Conscious capitalism field guide - Sisodia, Rajendra (Harvard Business Review Press, 2018)
You subscribe to the basic idea that business can do more than make money, but you're not sure how to act on that conviction or how to share it with the rest of your organization. The Conscious Capitalism Field Guide--the authoritative follow-up to the bestselling book Conscious Capitalism, by John Mackey, CEO of Whole Foods Market, and leadership expert Raj Sisodia--gives you the tools for sharing and implementing the principles of higher purpose and conscious business throughout your organization